Dinamika Penyebaran Agama di Wilayah Urban Semarang: Analisis Spasial menggunakan Sistem Informasi Geografis (SIG) - Zulfa Alfi Rohmah (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2023)
. This research aims to analyze the dynamics of religious spread in the urban areas of Semarang through a spatial analysis approach using Geographic Information System (GIS). By utilizing both secondary and recent primary data, this study delineates the patterns of religious spread across various neighborhoods and districts in Semarang. Through the application of GIS, the research produces thematic maps that vividly visualize the distribution of religions in a spatial context. The analysis results reveal diverse patterns of religious spread, with some areas exhibiting a high concentration of a particular religion while others demonstrate significant religious diversity. The importance of environmental factors in shaping the patterns of religious spread is also discussed in this study. The correlation analysis between the presence of places of worship, religious educational institutions, and other environmental variables provides additional insights into the factors influencing the distribution of religions in Semarang. The conclusions drawn from this research contribute to a deeper understanding of religious diversity in urban Semarang. The implications include the potential formulation of more effective development policies, strengthening tolerance among religious communities, and creating an inclusive environment amid the complexities of social and cultural diversity in the city. This research is expected to serve as a foundation for further studies and aid sustainable decision-making at the local level.